LEVI 3.0 – multiple criteria evaluation program for construction solutions - Zavadskas, Edmundas Kazimieras; Ustinovičius, Leonas; Turskis, Zenonas; Peldschus, Friedel; Messing, Danny (Journal of Civil Engineering and Management, 2002)
The paper considers the main methods employed to solve one-sided and two-sided problems of the game theory. For the one-sided problems only the method of solution “distance to the ideal point” is discussed. For the two-sided problems a distinction is made between games with rational behaviour and games against nature. The main principles of the strategies are as follows: simple min-max principle, extended min-max principle, Wald's rule, Savage criterion, Hurwicz's rule, Laplace's rule, Bayes's rule, Hodges-Lehmann rule. The questions transforming the decisionmaking matrix are considered: vectorial transformation, linear transformation, linear transformation according to Jüttler's or Stopp's method, non-linear transformation according to Peldschus. The article gives the description of a program package as well as an example of an investment variant estimation. The program LEVI 3.0 is a result of the cooperation between the VGTU and HTWK. This article provides description of a program package as well as an example of investment variant estimation to illustrate the application of methods described; efficiency problem of financial investment in construction or reconstruction in the health resort of Nida (Lithuania) is analysed.Frist Published Online: 30 Jul 2012